Reduced-crude protein diets in chicken-meat production: justification for an imperative. Issue 3 (2nd July 2020) - Greenhalgh, S.; Chrystal, P. V.; Selle, P. H.; Liu, S. Y.
SUMMARY: The justification for the chicken-meat industry to develop reduced-crude protein (CP) diets is compelling. Environment pollution by nitrogen and ammonia emissions can be improved, as a dietary reduction of 25 g/kg CP has been shown to generate a 25.8% reduction in N excretion. Bird welfare can be enhanced, as lower CP excretion improves litter quality and lessens the incidence of foot-pad dermatitis and related conditions. Flock health can be improved by reductions in the flow of undigested protein into the hindgut which, if unchecked, fuels the proliferation of potential pathogens at a time when in-feed inclusions of antibiotics are in decline. Moreover, reduced-CP diets have the potential to lessen feed ingredient costs as prices of 'synthetic' amino acids are likely to decrease due to economies of scale in production. The successful development and adoption of reduced-crude protein (CP) diets may reduce the chicken-meat industry's demand for sources of 'intact' protein, e.g. where soybean meal is dominant and in demand from many quarters. Using synthetic methionine, lysine and threonine in maize-soy diets has been shown to lead to a substantial reduction in dietary CP from 356 to 200 g/kg, along with reductions in soybean meal from 709 to 293 g/kg feed. Reductions of 40% of soyabean use in feed have been postulated.